Albedo factor determination of some selected 3d alloy samples - Turşucu, Ahmet (ELSEVIER, 2021)
The concept of albedo is used to describe the reflected incident radiation from a surface. Actually, this reflected radiation consists of two-component that enter the target samples and then backscattered from the target surfaces. The information about these components of the albedo phenomenon serves the solution of the albedo factor parameters that namely, the albedo number, energy, and dose. The albedo parameters of scientific importance 3d alloy samples have been measured and calculated, in this present work. The calculated albedo parameters plotted as a function of the mean atomic number. Eventually, this work shows that the albedo factor parameters of selected samples decrease with the increasing mean atomic number.
Keywords: Albedo dose; Albedo energy; Albedo factors; Albedo number; Gamma-ray scattering